Sleep quality and factors interfering with sleep among hospitalized elderly in medical units, Medan, Indonesia - Evi Karota-Bukit (Prince of Songkla University, 2003)
Thesis (M.N.S., Adult Nursing)--Prince of Songkla University, 2003